Multiclinic Observations on the Simplified Diet in PKU - Laurie Bernstein; Casey Burns; Melissa Sailer-Hammons; Angela Kurtz; Frances Rohr (Journal of Nutrition and Metabolism)
Phenylketonuria is an inborn error of metabolism that historically has been treated with a strict phenylalanine-restricted diet where all foods are weighed and measured. This is cumbersome and difficult for patients and caregivers, especially patients with high phenylalanine blood concentrations who often have neurocognitive deficits. The Simplified Diet is an alternative approach that allows for increased flexibility, promotes healthy food choices, and is easier to manage than a traditional diet for PKU. This paper describes the implementation of the Simplified Diet and outlines education, counseling strategies, and challenges encountered by three metabolic clinics in the United States.